Tertiary stratigraphic correlation of the Al Watiyate Region, Al Jabal Al Akhdar (Cyrena ica, NE Libya): An integration from previous studies. - M. El Oshebi, Farag; F. Fares, Fares; A. Aljuroushi, Ahmed; I. Altweel , Hamza (Libyan Journal of Science &Technology, 2026)
This paper provides a lithostratigraphic correlation of the Middle Eocene to Upper Miocene rock units of the Al Watiyate region of Al Jabal Al Akhdar, Cyrenaica, NE Libya. Data from this study were derived from measured vertical stratigraphic logs in six main studied areas: Daryanah-Al Abyar road cut, Wadi Al Kuf, Wadi Sidi Yossef, Wadi Al Juibiyah, Wadi Al Sukinyah, and Wadi Sidi Mohamed. This study needed to concentrate on the intricate details of the Tertiary carbonate rocks and how local structural or strato-structural disturbances may have shaped their spatial variations. In this regard, the main aim of this work is to establish a local lithostratigraphic cor relation among the investigated stratigraphic sections and to offer some insight into the com plexity of the Middle Eocene–Upper Miocene sequence concerning the stratigraphic framework. A method used for distinguishing rock units according to lithological characteristics is known as lithostratigraphic correlation. Based on the lithostratigraphic correlation, the Middle Eocene car bonate rock unit (Darnah Formation) is changed to Oligocene rock units (Al Bayda Formation) laterally in a SW to NE direction in the study region. In the southwest, the Darnah and Al Bayda formations disappear while the thickness of the Al Abraq Formation decreases. Furthermore the Al Faidiyah, Benghazi, and Wadi Al Qattarah formations, which are representative of the Miocene rock units, thickened more southwestward. The thickness variations are most likely related to paleotopography, where the rate of deposition differs from NE (high relief area) to SW (low relief area). The outcome of the northeastern uplift is due to tectonic movements. Regressive se quences characterize the Middle Eocene to Upper Miocene, indicating a periodic fall in sea level across geological time. The absence of Oligocene rock units in the Wadi Zazah and Wadi Belgares areas suggests tectonic uplift during the Early Eocene to Middle Miocene time. However, in Wadi Al Kuf, Wadi Azzad, and Wadi Al Backour, the terrain is gradually subsiding, and it appears that the sea was transgressed to continue the accumulation of Oligocene-Miocene sediments on top of the Eocene Formation. Lithostratigraphic correlation, Middle Eocene-Up per Miocene, paleotopography, Uplift, Al Watiyate region, Al Jabal Al Akhdar, NE Libya.